The effect of non-performing financing and financing to deposit ratio on Islamic banks financing in Indonesia - Gupita Permataningayu; Siti Mahdaria (Asian Journal of Islamic Management (AJIM), 2019)
Purpose: This study aims to analyze the effect of NPF (non-performing financing) and FDR (financing to deposit ratio) to the volume of financing in Indonesia Islamic Banks with third-party funds as a mediating variable. This research is a quantitative research.Methodology: The populations in this study are Bank Indonesia Publication Reports and other references from journals, research, internet, etc. Sampling was done by purposive sampling method Secondary data collection method used is documentation method. Data analysis techniques used in this research is the technique of mediation regression analysis, which uses multiple causal step method.Findings : The results show that NPF (non-performing financing) does not affect the volume of financing in Islamic commercial banks in Indonesia, FDR (financing to deposit ratio) does not affect the volume of financing in Islamic commercial banks in Indonesia, NPF (non-performing financing) has no effect on DPK (third party funds), FDR (financing to deposit ratio) has no effect on DPK (third party funds), DPK (third party funds) has a positive effect on the volume of financing in Islamic commercial banks in Indonesia, DPK partially mediates the effect of NPF (non-performing financing) to the volume of financing Islamic banks in Indonesia, DPK perfectly mediates the effect of FDR (financing to deposit ratio) to the volume of financing Islamic banks in Indonesia.Originality/Contribution: This is the first study to used Islamic banks selected for this research are Bank Muamalat Indonesia, Bank Syariah Mandiri, Bank Syariah Mega Indonesia and the data are taken from the tri-monthly report.